We are the weather : saving the planet begins at breakfast - Foer, Jonathan Safran, 1977- (Farrar, Straus and Giroux, 2019)
Some people reject the fact, overwhelmingly supported by scientists, that our planet is warming because of human activity. But do those of us who accept the reality of human-caused climate change truly believe it? If we did, surely we would be roused to act on what we know. Will future generations distinguish between those who didn<U+2019>t believe in the science of global warming and those who said they accepted the science but failed to change their lives in response? In We Are the Weather, Jonathan Safran Foer explores the central global dilemma of our time in a surprising, deeply personal, and urgent new way. The task of saving the planet will involve a great reckoning with ourselves<U+2014>with our all-too-human reluctance to sacrifice immediate comfort for the sake of the future. We have, he reveals, turned our planet into a farm for growing animal products, and the consequences are catastrophic. Only collective action will save our home and way of life. And it all starts with what we eat<U+2014>and don<U+2019>t eat<U+2014>for breakfast.